Facilitating Lifelong Learning in SMEs towards SDG4 - Hamburg, Ileana (Advances in Social Sciences Research Journal, 2020)
Technological innovations transform jobs, challenge existing competencies and require new sets of skills, or upskilling of old ones, particularly digital skills. In this context, Lifelong learning (LLL) plays and important role in addressing the skills gaps and means also creating and sustaining a positive attitude to learning for both professional and personal development. In this presentation, the author describes the situation of SMEs and LLL not only from literature but also from experience within the work with SMEs in some European projects. Besides other valorization activities of project results, the learning program offered to SME employees will be improved with new modules for mastering of important lifelong skills like digital ones.